2015
DOI: 10.1542/peds.2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Urinalysis for Urinary Tract Infection in Infants <3 Months of Age

Abstract: The 2011 American Academy of Pediatrics urinary tract infection (UTI) guideline suggests incorporation of a positive urinalysis (UA) into the definition of UTI. However, concerns linger over UA sensitivity in young infants. Infants with the same pathogenic organism in the blood and urine (bacteremic UTI) have true infections and represent a desirable population for examination of UA sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 24 publications
(27 reference statements)
6
88
3
Order By: Relevance
“…As a compromise, if it is not possible for a laboratory to include a Gram stain or hemocytometer WBC count, some laboratories move the reporting threshold for a significant bacterial countdown to Ն10 4 CFU/ml (Ն10 7 CFU/liter in SI units) or even lower. This practice is supported by a recent study (17) showing that, in infants with bacteremic UTI (not neutropenic), which by definition excludes infants with contaminated urine cultures or asymptomatic bacteriuria, either the leukocyte esterase (LE) test or the nitrite test had a sensitivity of 97.6% and a specificity of 93.9% in detecting UTI, which is much higher than those values previously reported in this population. Standard microscopic detection of pyuria showed a similar sensitivity, but the specificity was considerably lower (around 65%), which probably reflects the fact that various sub- optimal definitions using centrifuged urine samples were used.…”
Section: Urinalysismentioning
confidence: 66%
See 3 more Smart Citations
“…As a compromise, if it is not possible for a laboratory to include a Gram stain or hemocytometer WBC count, some laboratories move the reporting threshold for a significant bacterial countdown to Ն10 4 CFU/ml (Ն10 7 CFU/liter in SI units) or even lower. This practice is supported by a recent study (17) showing that, in infants with bacteremic UTI (not neutropenic), which by definition excludes infants with contaminated urine cultures or asymptomatic bacteriuria, either the leukocyte esterase (LE) test or the nitrite test had a sensitivity of 97.6% and a specificity of 93.9% in detecting UTI, which is much higher than those values previously reported in this population. Standard microscopic detection of pyuria showed a similar sensitivity, but the specificity was considerably lower (around 65%), which probably reflects the fact that various sub- optimal definitions using centrifuged urine samples were used.…”
Section: Urinalysismentioning
confidence: 66%
“…Furthermore, combined with the data from Schroeder et al (17), which showed the excellent performance of the dipstick in predicting bacteremic UTIs in infants less than 3 months of age, these studies suggest that microscopic methods, such as Gram stain and hemocytometer WBC counts, may be supplanted by either manual or automated methods for the detection of pyuria or bacteriuria in children. Whether these findings hold true if a lower threshold for significant bacteriuria is used in children, i.e., 10 4 CFU/ml, and how different automated testing systems compare to one another at different bacterial thresholds remain to be studied.…”
Section: Urinalysismentioning
confidence: 79%
See 2 more Smart Citations
“…However, few would disagree that bacteremic UTI (isolation of the same pathogenic organism from the blood and urine) represents true infection. Because of the entities of asymptomatic bacteruria and contamination, the lack of a reliable gold standard for the diagnosis of UTI will be a perpetual problem, 1 and we believe that bacteremic UTI offers a unique way to assess the performance of the UA in an infant who has a true infection.…”
Section: Authors' Responsementioning
confidence: 99%